2003
DOI: 10.1007/s11746-003-0740-y
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stability of walnut oils extracted with supercritical carbon dioxide

Abstract: Supercritical carbon dioxide (SC‐CO2) was used to partially defat walnuts, and the oxidative stability of the extracted walnut oils was assessed. The SC‐CO2‐extracted oils were less stable during accelerated storage in the dark than was pressed walnut oil, as determined by PV, headspace analysis by solid‐phase microextraction, and sensory methods. The SC‐CO2‐extracted oils, however, exhibited greater photo‐oxidative stability than did pressed walnut oil by all of these methods, possibly because of the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 16 publications
6
17
0
1
Order By: Relevance
“…Oxidative stability of the camelina seed oils extracted with SC‐CO 2 was lower than that of cold pressed oils. Crowe and White () reported that oxidative stability of walnut oil obtained by SC‐CO 2 extraction was lower than cold pressed walnut oil, which is in good agreement with our findings.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Oxidative stability of the camelina seed oils extracted with SC‐CO 2 was lower than that of cold pressed oils. Crowe and White () reported that oxidative stability of walnut oil obtained by SC‐CO 2 extraction was lower than cold pressed walnut oil, which is in good agreement with our findings.…”
Section: Resultssupporting
confidence: 93%
“…There are limited reports on the extraction and composition of camelina seed oil, and to the best of our knowledge, there is only one report on the SC‐CO 2 extraction of camelina seed oil (Belayneh and others ). Crowe and White () and List and Friedrich () have studied oxidative stabilities of walnut oil and corn germ oil, soybean oils, and cottonseed oils extracted by pure SC‐CO 2 , respectively. Therefore, the main objective of this study was to determine the effect of extraction method, namely, SC‐CO 2 , ethanol‐modified SC‐CO 2 , cold press, and hexane, on the oxidative stability of the camelina seed oil using differential scanning calorimeter (DSC).…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the highest tocopherol amounts found in SC CO 2 extracted oils, their oxidative stability values were lower than those obtained from press-extracted oils. These results agree with data obtained by Calvo et al (1994), Oliveira et al (2002) and Crowe and White (2003) indicating that WO obtained by SC CO 2 is less protected against oxidation. One possible explanation for these findings has been focussed on the oxygen content of CO 2 used for SC extraction.…”
Section: Supercritical Co 2 Extractionsupporting
confidence: 92%
“…Oil extraction by supercritical carbon dioxide (SC-CO 2 ) has been associated with greater thermal oxidative instability of the oils than by solvent or extruder extraction methods (Calvo et al , 1994;List and Friedrich, 1989). Crowe and White (2003) also observed that SC-CO 2 extracted walnut oils were less stable than pressed walnut oils during accelerated storage in the dark, as determined by PV, headspace analysis by solid-phase microextraction, and sensory methods. However, the SC-CO 2 -extracted oils exhibited greater photo-oxidative stability than their pressed counterparts, possibly due to the presence of chlorophylls in the pressed oil.…”
Section: 36mentioning
confidence: 99%
“…The increased stability of SC-CO 2 -extracted oils to light-induced oxidation is therefore important. Oxidative stability indices and tocopherol contents were however signifi cantly (p < 0.05) lower in the SC-CO 2 -extracted oils than in pressed walnut oils (Crowe and White, 2003). Nejad et al (2002) studied the effect of various drying methods (sun drying, bin dryer, vertical continuous dryer, vertical cylindrical dryer and funnel vertical dryer) on the quality of pistachio nuts.…”
Section: 36mentioning
confidence: 99%